IMPLEMENTASI STANDAR PELAYANAN MINIMAL RUMAH SAKIT (Studi Standar Pelayanan Minimal RSUD Harapan dan Doa Kota Bengkulu Berdasarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 129 Tahun 2008) - Rahiman Dani; Eriani, Septi; Henny Aprianty; Heru Purnawan (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
This research was conducted with the following objectives: 1. Analyzing the status of implementation of minimum service standards at Pintu Harapan Hospital, Bengkulu City based on Regulation of the Minister of Health of the Republic of Indonesia Number 129 of 2008; 2. To find out the factors that influence the implementation of minimum service standards in RSUD hospitals. The hopes and prayers of the City of Bengkulu are based on the Regulation of the Minister of Health of the Republic of Indonesia Number 129 this year. The type of research used in this research is descriptive with a qualitative approach. This research is descriptive research which aims to collect information about current conditions and symptoms. The data collection techniques used were observation, interviews and documentation methods. Data analysis techniques use data reduction, data presentation (data presentation), and drawing conclusions and validation. The results of this research indicate that the implementation of minimum service standards at Pintu Harapan Hospital, Bungkulu City is very good. This can be seen from the factors that interact and influence policy implementation based on George Edward III's theory. This means, (1) the communication aspect is successful and implementers implement it clearly and consistently to influence policy objectives and understand the policy content; Policy goals and objectives. (2) The resource aspect consists of the number of device resources, device features and capabilities. Even though the number of resources is sufficient, several locations in the hospital have several employees with inappropriate educational backgrounds. Although the facilities and equipment are quite good, there is still room for improvement. (3) Supported by the attitudes and behavior of the apparatus during the implementation of the SPM policy, the disposition aspect shows very good improvement. (4) Aspects of the bureaucratic structure through SPM standard operating procedures and procedures (SOP) are well controlled, but consistency only needs to be improved through stricter rules.